Additive Anticonvulsant Profile and Molecular Docking Analysis of 5,5′-Diphenylhydantoin Schiff Bases and Phenytoin - Jana Tchekalarova; Petar Todorov; Miroslav Rangelov; Tsveta Stoyanova; Nadezhda Todorova (Biomedicines, 2023)
Four 5,5′-diphenylhydantoin Schiff bases possessing different aromatic species (SB1–SB4) were recently synthesized and characterized using spectroscopic and electrochemical tools. The present study aimed to ascertain the anticonvulsant activity of the novel phenytoin derivatives SB1-Ph, SB2-Ph, SB3-Ph, and SB4-Ph, containing different electron-donor and electron-acceptor groups, and their possible mechanism of action. The SB2-Ph exhibited the highest potency to suppress the seizure spread with ED50 = 8.29 mg/kg, comparable to phenytoin (ED50 = 5.96 mg/kg). While SB2-Ph did not produce neurotoxicity and sedation, it decreased locomotion and stereotypy compared to control. When administered in combination, the four Schiff bases decreased the phenytoin ED50 by more than 2× and raised the protective index by more than 7× (phenytoin+SB2-Ph). The strongest correlation between in-vivo and docking study results was found for ligands’ interaction energies with kappa and delta receptors. These data, combined with the worst interaction energies of our ligands with the mu receptor, suggest that the primary mechanism of their action involves the kappa and delta receptors, where the selectivity to the kappa receptor leads to higher biological effects. Our findings suggest that the four Schiff bases might be promising candidates with potential applications as a safe and effective adjuvant in epilepsy.